Moralidade e violência nas escolas na visão dos professores - Costa, Rodrigo César [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Violence, multifaceted and socially recurring phenomenon, long raided the school walls. There are several reports of outbreaks of violence in school ranging from the symbolic, verbal to physical violence. Thus, this study aims to understand and analyze what teachers think of the 6th year of elementary school, two public schools in the city of Maringá (PR), located in different neighborhoods with different histories and violence on school violence and the development of human morality and their possible relationships. The proposal to develop this work according to the contributions of the theory of moral development has as its foundation the methodology of hermeneutic qualitative nature. In qualitative research the word hermeneutics refers to the science of qualitative interpretation of what is said. Unlike quantitative proposals, this type of research that most interests the investigator is in-depth analysis of the studied phenomenon. As a tool for data collection used the semi-structured interview. In the first chapter, we conducted a brief discussion about violence in school discipline, bullying, and discuss the relationship between family and school. The next chapter presents the moral theory of Piaget (1932/1994), mainly rescuing concepts from his book moral judgment in children and the theory Kohlberg (1992). Around the psychology of human morality, we also discuss what is moral and ethical to La Taille (2006), briefly cite some conceptions of morality and ethics today and resumed some concepts of philosophy, as Kant (1785/2005) in Metaphysics of customs. In the third chapter, we present the possible relationships between psychology and morality of violence in school, which is the focus of this study. In the fourth chapter we describe the methodology and chapter five we present our results and analysis. Finally, we weave our final considerations. We conclude that theories of moral...

A violência, fenômeno multifacetado e socialmente recorrente, há muito invadiu os muros das escolas. Diversos são os relatos sobre manifestações de violência na escola que vão desde a violência simbólica, verbal até a física. Sendo assim, este estudo tem como objetivo conhecer e analisar o que pensam professores do 6º ano do Ensino Fundamental, de duas escolas públicas da cidade de Maringá (PR), localizadas em diferentes bairros e com diferentes históricos de violência, sobre a violência escolar e o desenvolvimento da moralidade humana e suas possíveis relações. A proposta de desenvolver este trabalho, baseado nos aportes da teoria do desenvolvimento moral, teve como alicerce a metodologia de cunho qualitativo hermenêutico. Na pesquisa qualitativa, a palavra hermenêutica refere-se à ciência da interpretação qualitativa do que é dito. Diferentemente das propostas quantitativas, nesse tipo de pesquisa o que mais interessa ao investigador é a análise aprofundada do fenômeno pesquisado. Como instrumento para a coleta de dados utilizou-se a entrevista semiestruturada. Este estudo traz uma breve discussão acerca da violência na escola, indisciplina, bullying, além de discutir as relações entre família e a escola. Aborda, também, a teoria moral de Piaget (1932/1994), resgatando, em especial, conceitos do seu livro O Juízo moral na criança e a teoria de Kohlberg (1992). Em torno da psicologia da moralidade humana, são discutidas brevemente algumas concepções acerca da moral e ética na atualidade, com destaque para as contribuições de La Taille (2006). São ainda retomados alguns conceitos da filosofia, como Kant (1785/2005) em Fundamentos da Metafísica dos Costumes. São estabelecidas, em especial, as possíveis relações entre a Psicologia da Moralidade e a violência na escola, que é o foco deste estudo. Enfim, o presente estudo permitiu concluir que as teorias do...
Keywords: Violencia escolar; Ética; Assédio nas escolas; Harassment